Alkali Activated Concrete with Steel Slag Aggregate for Concrete Pavements - Nitendra Palankar, Dr; Mithun B M, Dr; A.U.Ravishankar, Dr (International Journal of Engineering and Technology, 2018)
In the present study, an attempt is made to investigate the usability of steel slag, which is a byproduct from the iron and steel industry, as coarse aggregates in alkali activated slag/ fly ash concrete mixes. The mix design for alkali activated slag/ fly ash concrete mixes was optimized and further steel slag coarse aggregates were incorporated in the optimized alkali activated slag/ fly ash concrete mixes mix by replacing natural coarse aggregates at different replacement levels (0%, 25%, 50%, 75% and 100% by volume). The mechanical properties were studied in detail. The flexural fatigue behavior of concrete mixes were investigated The experimental results showed that alkali activated slag/ fly ash concrete mixes with steel slag aggregates display slightly lower mechanical strength as compared to natural aggregates. The fatigue life of alkali activated slag/ fly ash concrete mixes was found to decrease with the inclusion of steel slag aggregates. The performance of steel slag aggregates in alkali activated slag/ fly ash concrete mixes was found satisfactory for use in pavement quality concrete.Â